HUMAN DIGNITY IN INDIAN DEMOCRACY: ALREADY OR NOT YET? - Palathinadiyil, Anish Mathew (Asian Horizons, 2020)
The article aims at perceiving the concept of human dignity in the Indian democracy based on the present socio-political situation. The pertaining question the article treats is whether human dignity is already realized or it is an ideal yet to be realized in the present situation of the nation. The first part of the article makes an investigation into the notion of human dignity as presented in the Indian constitution. The preamble, fundamental rights and some significant judgments by the judiciary emphasize human dignity. However, the present socio-political situation gives a different picture. In India democracy is flawed, politics is criminalized, dissents and media are silenced, administrative structures are being nullified, widespread corruption, violence, lynching, casteism, pro-rich economic policies, post-truth culture and attacks on women constantly challenge human dignity. The second part of the article tries to understand the theological and biblical foundations of human dignity. Based on this, the political ramifications of human dignity are analysed. Steps to regard Indian constitution as a sacred book, to take national pledge seriously and to actively participate in the democratic processes are proposed.